2005
DOI: 10.1172/jci24762
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipid antigen induces long-term natural killer T cell anergy in mice

Abstract: Natural killer T (NKT) cells recognize glycolipid antigens presented by the MHC class I-related glycoprotein CD1d. The in vivo dynamics of the NKT cell population in response to glycolipid activation remain poorly understood. Here, we show that a single administration of the synthetic glycolipid alpha-galactosylceramide (alpha-GalCer) induces long-term NKT cell unresponsiveness in mice. NKT cells failed to proliferate and produce IFN-gamma upon alpha-GalCer restimulation but retained the capacity to produce IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
464
3
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(522 citation statements)
references
References 54 publications
37
464
3
2
Order By: Relevance
“…Autoimmunity prevention correlated with the ability of aGalCer to induce iNKT cell anergy and to strongly suppress their IFN-g production while IL-4 production was less inhibited [33]. Interestingly, we have observed that aGalCer treatment suppressed not only IFN-g by iNKT cells but also their IL-17 production whereas it does not inhibit IL-10 production (Fig.…”
Section: Cd4 à Inkt Cells Containing Inkt17 Cells Enhance the Incidenmentioning
confidence: 57%
“…Autoimmunity prevention correlated with the ability of aGalCer to induce iNKT cell anergy and to strongly suppress their IFN-g production while IL-4 production was less inhibited [33]. Interestingly, we have observed that aGalCer treatment suppressed not only IFN-g by iNKT cells but also their IL-17 production whereas it does not inhibit IL-10 production (Fig.…”
Section: Cd4 à Inkt Cells Containing Inkt17 Cells Enhance the Incidenmentioning
confidence: 57%
“…As repeated NKT cell stimulation with free glycolipid is known to induce anergy, [36][37][38] we performed a dose response study using single injections of a-GalCer. A significant increase in overall survival time was observed with the highest dose (i.p.…”
Section: Glycolipid Treatments Reduce Metastasismentioning
confidence: 99%
“…This would be in good agreement with the postulated role of the iNKT cell population as an 'innate' sensor of the immune system that links innate and adaptive immunity. Indeed, upon antigenic stimulation, iNKT cells expand for a few days and then quickly contract without generating memory cells [81].…”
Section: How Do Inkt Cells Get Activated? Cognate Recognition and Actmentioning
confidence: 99%